1999
DOI: 10.1002/(sici)1096-8628(19990129)82:3<219::aid-ajmg5>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Thumb/hallux duplication and preaxial polydactyly type I

Abstract: It was recently shown that hand postaxial polydactyly differed from foot postaxial polydactyly. The aim of this work was to test whether thumb and hallux duplication also had different clinical and epidemiological characteristics, depending on limb involvement. We studied 920 newborn infants with first digit duplication, ascertained among 3,444,374 births by the Latin-American Collaborative Study of Congenital Malformations (ECLAMC), from 1967 to 1995. Since biphalangeal thumb duplication or hallux duplication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Therefore, our findings strongly argue for a role of environmental influence on the etiology of PPD1. Notably, the association of low birthweight with increased risk of isolated PPD1 has been reported previously [12]. …”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Therefore, our findings strongly argue for a role of environmental influence on the etiology of PPD1. Notably, the association of low birthweight with increased risk of isolated PPD1 has been reported previously [12]. …”
Section: Discussionmentioning
confidence: 60%
“…One of the largest studies of 5,171 children with a variety of digital anomalies including polydactyly, syndactyly and adactyly demonstrated that the mothers of these children were more likely to suffer from anemia, cardiac disease, lung disease, oligohydramnios, polyhydramnios, or pregnancy-associated hypertension [15]. Other implicated maternal risk factors include vaginal bleeding in the first trimester [12], and diabetes [2,15,16]. In this study, there were no PPD1 cases born to mothers with diabetes type I or II, thus it is unlikely to be an important risk factor.…”
Section: Discussionmentioning
confidence: 99%
“… 2009 ). Furthermore, Orioli and Castilla ( 1999 ) showed that most cases of isolated preaxial polydactyly of the foot occur sporadically. However, in a molecular review by Johnston et al.…”
Section: Discussionmentioning
confidence: 99%
“…Usually observed as unilateral form, while in bilateral cases, hands are more preferentially affected and the left hand PPD are rare as compared to right hand PPD ( Malik et al, 2014 ). There is a low occurrence of familial reappearance and high prevalence of affected males than females ( Orioli and Castilla, 1999 ). Heptadactyly or hexadactyly is also a type of thumb polydactyly in which triplication of thumb occurs, resulting in seven digits ( Zuidam et al, 2008 ).…”
Section: Preaxial Polydactyly (Ppd)mentioning
confidence: 99%